Plan de e-commerce para articulos fabricados en cuero de la tienda Erazo de Quevedo, creando un web site - Erazo Casanova, Karina Cecilia (2012)
Over the years various technologies have emerged that in his time achieved some amazing changes in the humanity in the different areas that the make up. One of these technologies, which has significantly impacted the entire world is because the Internet was created and opened up new opportunities for each of the business. The leather industry has been characterized by being one of the most dynamic sectors of the economy of Ecuador, where currently reaches high quality standards that are being tapped in good shape by our markets comma is the case of the store that sells Erazo portfolios or accessories made in leather.accessories made in leather. This paper presents a viable alternative to doing the marketing of bags, purses and other items manufactured in leather toward local and international markets, as these we offer a series of opportunities and benefits without leaving of side the risks and challenges that this implies. On the other hand this is a good alternative for our products to be promoted by means of the web site. Currently the shop Erazo has the interest to increase their income, while the need to innovate this marketing process with the technification of the sales system to achieve their stated objectives to achieve find new niche markets both local and national The world through the Internet and in general the use of technology has enabled us to establish channels of communication and sales that are fundamental to access the information of international marketing. The use of this tool of communication, including social networks with more than 500 million users and in constant growth becomes very important at the time to find new consumers of our products. The implementation of a new process for the marketing store ERAZO, belonging to the family of the Erazo Cross city of Quevedo, implementing a web site to facilitate the customer to purchase the products manufactured in leather, comfortably and without losing time. It is therefore justified the realization of this project; making the owners of this business promoting their products to a global market. Some objectives were raised as: Design the plan for e-commerce for items manufactured in leather shop Erazo Quevedo, creating a website. and between the specific were: make the internal and external analysis of the business making use of the SWOT matrix; to know which is the frequency and the place where they connect to the internet service customers of the shop Erazo by means of the survey; investigate the intention of buying over the internet of the store's customers. Erazo through continuing home survey; Perform internal and external analysis of the business making use of the SWOT matrixThe hypothesis was: Customers of the shop Erazo are willing to receive offers of products manufactured in leather by means of a website.